2020
DOI: 10.1371/journal.pone.0231507
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of anti-PDL-1 with ablative radiation comparing to other regimens with same biological effect dose based on different immunogenic response

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A super flab bolus material of 1.5 cm was located above the tumor. The distance between the source and mouse skin was 100 cm [14,15].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A super flab bolus material of 1.5 cm was located above the tumor. The distance between the source and mouse skin was 100 cm [14,15].…”
Section: Treatmentmentioning
confidence: 99%
“…We utilized three different fractionation schemes; a single high-dose, hypofractionated, and hyperfractional (conventional) RT with the same biological effect dose (BED). Compared to another regimen, a single high dose RT augmented the numbers of immune cells in the TME and was the most efficient in combination with αPDL-1 mAb [14]. Therefore, we decided to examine the potency of combination therapy of single high dose RT plus anti-CD47 immune checkpoint inhibitor compared to single therapies for tumor control.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the timing of these two treatments must be considered for optimal tumor regression. Several other studies and clinical trials have expanded on and shown the significant anti-tumor effects of radiotherapy combined with PD-L1 inhibitors or regulatory T cell depletion (32)(33)(34)(35)(36)(37)(38).…”
Section: Immune System Suppressionmentioning
confidence: 99%
“…In contrast to previous model attempts, it accounts for the dynamics of cell death considering a time distribution of immune response after irradiation, and it will be benchmarked against a broad set of experimental preclinical data taken from the literature. 1,[8][9][10][11][12][13][14][15][16] Methods and Materials…”
Section: Introductionmentioning
confidence: 99%